Time to eat: household production under increasing income inequality - Daniel S. Hamermesh (Institute for the Study of Labor (IZA), 2006)
Eating requires the food materials that make up meals and also time devoted to buying food, preparing meals and eating them, and cleaning up afterwards. Using time-diary and expenditure data for the U.S. for 1985 and 2003, I examine how income and time prices affect time and goods inputs into this household-produced commodity. Focusing on these two years, between which income and earnings inequality increased, allows examining how household production is affected by changing economic opportunities. The results demonstrate that both inputs into eating increase with income, and that higher time prices at a given level of income reduce time inputs. Over this period the goods intensity of producing this commodity increased, especially at the lower part of the income distribution, and the average time input dropped substantially. The results are consistent with goods-time substitution in eating being relatively difficult and with substitution becoming relatively more difficult as production expands. This is confirmed by direct estimates using matched time-use and food spending data on the same households for 2003 and 2004. The findings imply that projecting food expenditures alone overestimates the amount spent on food in a growing economy.
Keywords: J22; Q11; 330; time use; food purchases; income distribution; Privater Haushalt; Hausarbeit; Zeit; Einkommensverteilung; USA